Zapisz w jak najprostszej postaci
(nie wiem czy 35 wystarczy bo zadaje zadanie 1 raz.)

1.2(x+1)
2.y+(y+1)
3.2(x+2)
4.-(1-y)
5.x-(x-2)
6.2(y+1)+1
7.x-(x-6)
8.1+(2y-4)
9.(y+2)-1
10.2(x+1)+1
11.y+(2y-1)
12.2(x-1)
13.1+x+1
14.5y+5-(5-3y)+2y
15.2x+7-2x
16.x+2(x+1)
17.3(x-1)
18.3(y-1)+5
19.3x-3(x-1)
20.2(y-1)+y
21.2(y+1)-y
22.4+y+5-y
23.2(x-2)-x
24.y+2y
25.3(x+1)
26.(x-2)-1
27.7(x+3)-6(x+4)
28.(x+4)-1
29.2(y+1)+(y-1)
30.2x+y-x
31.x+5y-x
32.2(x-2)
33.5(x+7)-5x
34.2(x-1)+2
35.5(x+4)-(5x-3)

3

Odpowiedzi

2009-11-25T18:12:21+01:00
1.2(x+1)=2x+1
2.y+(y+1)=2y+1
3.2(x+2)=2x+4
4.-(1-y)=-1+y
5.x-(x-2)=2
6.2(y+1)+1=2y=3
7.x-(x-6)=6
8.1+(2y-4)=2y-3
9.(y+2)-1=y+1
10.2(x+1)+1=2x+3
11.y+(2y-1)=3y-1
12.2(x-1)=2x-2
14.5y+5-(5-3y)+2y=4y
15.2x+7-2x=+7
16.x+2(x+1)=3x+2
17.3(x-1)=3x-3
18.3(y-1)+5=3y-3+15
19.3x-3(x-1)=3
20.2(y-1)+y=3y-2
21.2(y+1)-y=y+2
22.4+y+5-y=9
23.2(x-2)-x=x-4
24.y+2y=3y
25.3(x+1)=3x+3
26.(x-2)-1=x-3
28.(x+4)-1=x+3
29.2(y+1)+(y-1)=2y
30.2x+y-x=x+y
31.x+5y-x=5y
32.2(x-2)=2x-4
33.5(x+7)-5x=35
34.2(x-1)+2=x+2
2009-11-25T18:14:54+01:00
1)2x+2
2)y²+y
3)2x+4
4)y-1
5)2
6)2y+3
7)6
8)2y-3
9)y+1
10)2x+3
11)2y
13)x+2
14)10y
15)7
16)3x+2
17)3x-3
18)3y+2
19)3
20)3y-2
21)y+2
22)9
23)x-4
24)3y
25)3x+3
26)x-3
27)7x+7-6x-24=x-17
28)x+3
29)2y+2+y-1=3y+1
30)x+y
31)y
32)2x-4
33)35
34)2x
35)5x+20-5x+3=23
2009-11-25T18:15:42+01:00
1. 2(x+1)=2x+2
2. y+(y+1)=y²+y
3. 2(x+2)=2x+4
4. -(1-y)=-1+y
5. x-(x-2)=x²-2x
6. 2(y+1)+1=2y+2+1=2y+3
7. x-(x-6)=x²-6x
8. 1+(2y-4)=1+2y-4=-3+2y
9. (y+2)-1=-y-2
10. 2(x+1)+1=2x+2+1=2x+3
11. y+(2y-1)=2y²-y
12. 2(x-1)=2x-2
13. 1+x+1=2+x
14. 5y+5-(5-3y)+2y=5y+25+15y+2y=22y+25
15. 2x+7-2x=7
16. x+2(x+1)=x+2x+2=3x+2
17. 3(x-1)=3x-3
18. 3(y-1)+5=3y-3+5=3y+2
19. 3x-3(x-1)=3x-3x+3=3
20. 2(y-1)+y=2y-2+y=y-2
21. 2(y+1)-y=2y+2-y=y+2
22. 4+y+5-y=9
23. 2(x-2)-x=2x-2-x=x-2
24. y+2y=3y
25. 3(x+1)=3x+3
26. (x-2)-1=x-2-1=x-3
27. 7(x+3)-6(x+4)=7x+21-6x+24=x+45
28. (x+4)-1=x+4-1=x+3
29. 2(y+1)+(y-1)=2y+2+y-1=3y+1
30. 2x+y-x=x+y
31. x+5y-x=5y
32. 2(x-2)=2x-4
33. 5(x+7)-5x=5x+35-5x=35
34. 2(x-1)+2=2x-2+2=2x
35. 5(x+4)-(5x-3)=5x+20-5x+3=23